Motion Scenes Direction Treatment in TV Drama: عشتار حبيب (Al-Academy, 2019)
The sense of motion generates a sense of the subject of action. The movement of the camera, the movement of actors, the movement of colors and lights, and other elements of the visual discourse, work together to enrich the image with a complete dynamic flow to reach the recipient. The research subject has been identified under the title "Motion Scenes Dramatic Treatment in TV Drama". The research is divided into an introduction and two theoretical sections in the theoretical framework:The first section: The motion in TV drama in which the researcher dealt with the concept of motion and its types and the expressive and aesthetic role in television drama. The second section dealt with the elements of the visual and audio language in the motion scenes. In this section the types of scenes and the angles of photography have been searched, and also the sizes of the shots and the recognition of lighting and color and editing have been addressed. At the end of the second section, the researcher identified the theoretical framework indicators, which will be adopted as tools for the analysis of the sample.The researcher, after analyzing the research sample, came up with the most prominent results as follows: The motion is a basic structure that must be present in the direction treatments in the TV drama to detect the evolution and complexity of events until the solution, as it appeared in the research sample. The research ends with a list of sources and a summary in English.